The Influence of Sociodemographic Background on Active Transportation: A Case Study of Bangsar and Shah Alam, Malaysia - Harumain, Yong Adilah Shamsul; Koting, Suhana; Rosni, Nur Aulia; Ibrahim, Nuraihan (Frontiers in Built Environment, 2022)
An essential element for promoting sustainable urban transport is active transportation. Many factors are associated with walkability, such as individual characteristics, socio-demography, and distance. This paper presents the findings on active transportation use relating to socio-demographic background. Using a questionnaire survey as an instrument, the study was performed in Bangsar and Shah Alam, Malaysia, via stratified random sampling. The binomial logistic regression model and analysis of variance (ANOVA) were used for analysing the data from 325 respondents statistically. The ANOVA demonstrated that education level and occupational status statistically influenced the home–public transportation station distance. The study outcomes could benefit many sectors, such as urban planning, transportation, health, and education. An enhanced understanding of the findings can contribute to decision-making among the relevant authorities for facilitating active transportation.